2017
DOI: 10.1159/000452965
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Kidney Disease: Hidden Consequences of the Epidemic

Abstract: Obesity has become a worldwide epidemic, and its prevalence has been projected to grow by 40% in the next decade. This increasing prevalence has implications for the risk of diabetes, cardiovascular disease, and also for chronic kidney disease. A high body mass index is one of the strongest risk factors for new-onset chronic kidney disease. In individuals affected by obesity, a compensatory hyperfiltration occurs to meet the heightened metabolic demands of the increased body weight. The increase in intraglomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 92 publications
2
58
1
1
Order By: Relevance
“…Overweight and obesity is an important risk factor for the development of several non-communicable diseases (NCDs) like diabetes mellitus,8 hypertension,9 cardiovascular diseases,10 cancer11 and chronic kidney diseases 12. In addition, overweight and obese women experience complications during pregnancy (gestational diabetes mellitus, pre-eclampsia and eclampsia) more frequently than women of normal body weight 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity is an important risk factor for the development of several non-communicable diseases (NCDs) like diabetes mellitus,8 hypertension,9 cardiovascular diseases,10 cancer11 and chronic kidney diseases 12. In addition, overweight and obese women experience complications during pregnancy (gestational diabetes mellitus, pre-eclampsia and eclampsia) more frequently than women of normal body weight 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, obesity acts as one of the most influential risk factors for chronic kidney diseases. 9 Nonalcoholic fatty liver disease (NAFLD) is strongly associated with obesity. However, NAFLD is almost always asymptomatic; elevated levels of liver transaminase could be detected in children.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the risk of cardiometabolic disorders, as well as liver and kidney dysfunctions. 8,9 The path analysis of a previous phase of this study indicated that body mass index (BMI) is the strongest determinant for cardiovascular risk factors; moreover, other variables such as unhealthy diet and low physical activity impressed their indirect effects through BMI. Many studies have evaluated the association between predisposing factors including lifestyle habits, exposure to environmental chemicals, socioeconomic status, and chronic diseases.…”
Section: Introductionmentioning
confidence: 91%
“…It is possible that these insecurities are exacerbated on geosocial-networking applications where profiles contain pictures as well as height and weight measurements as factors determining initial contact. Alternatively, obese MSM may have other health issues, such as chronic kidney disease, that prevent them from being started on PrEP 27 28. More research is needed to understand the association between obesity and decreased PrEP uptake.…”
Section: Discussionmentioning
confidence: 99%